The Level of Independence and Social Activity with the Life Satisfaction of the Elderly at Panti Bhakti Luhur Sidoarjo - Sri Anik Rustini; Raudatul Jannah; Astrida Budiarti; Ninik Ambar Sari; Ceria Nurhayati; Merina Widyastuti (Universitas STRADA Indonesia, 2022)
Background: Many factors are related to life satisfaction in the elderly, one of which is the level of independence and social activity. This study aims to determine the level of independence and social activity with the life satisfaction of the elderly at Panti bhakti Luhur Sidoarjo. Purpose: The purpose of the study was to determine the independence and social activities with the life satisfaction of the elderly at Panti bhakti Luhur Sidoarjo. Methods: The sampling technique used non-probability sampling with accidental sampling. The population of this study was 108 people and the research sample obtained was 85 elderly people aged over 60 years at Panti Bhakti Luhur Sidoarjo. To assess the level of independence using a Katz Index questionnaire, to assess social activity using a social activity questionnaire, to assess life satisfaction using the SWLS (Satisfaction With Life Scale) questionnaire. The data is then tested using Spearmen Rho Correlation. Results: Research shows that there is a relationship between the level of independence and life satisfaction of 0.001 (?<0.05) and social activities with life satisfaction of 0.000 (?<0.05). Conclusion: The level of independence and social activities related to the life satisfaction of the elderly requires support from the family and related agencies in developing elderly activities to increase life satisfaction by motivating and helping the elderly to be able to train the level of independence and social activities.